Implementation of Simple Linear Regression for Predicting of Students’ Academic Performance in Mathematics - Hasanah, Herliyani; Farida, Anisatul; Yoga, Pineda Prima (Universitas Islam Negeri Sunan Kudus, 2022)
Predicting student academic performance is an interesting thing to research. Student academic performance can be used to determine the level of student mastery of the subject matter that has been delivered. This research uses academic and personal data of secondary students on mathematics subject scores in Portugal with 395 data records. The purpose of this research is to study how linear regression is applied in order to determine the predictive results of students' academic performance. Prediction evaluation is done by calculating attribute correlation with class, Root Mean Squared Error (RMSE), and Mean Absolute Percentage Error (MAPE). The results of this research test the accuracy obtained linearly with correlation results, namely class failure (d) has the smallest RMSE and MAPE with an RMSE value of 1.148 and a MAPE of 9.82% of students' academic performance in mathematics. The results of the data analysis show that the failure variable has a positive effect on G3, where the probability value of the F test, the significance value for the simultaneous failure effect on G3 is 0.006 <0.05 and from the analysis of the coefficient of determination it is known that the failures variable is significant to the dependent variable with a large influence 63,8 % (model 2). Memprediksi prestasi akademik mahasiswa merupakan hal yang menarik untuk diteliti. Prestasi akademik siswa dapat digunakan untuk mengetahui tingkat penguasaan siswa terhadap materi pelajaran yang telah disampaikan. Penelitian ini menggunakan data akademik dan data pribadi siswa sekolah menengah pada nilai mata pelajaran matematika di Portugal dengan 395 data record. Tujuan dari penelitian ini adalah untuk mempelajari bagaimana regresi linier diterapkan untuk menentukan hasil prediksi prestasi akademik siswa. Evaluasi prediksi dilakukan dengan menghitung korelasi atribut dengan kelas, Root Mean Squared Error (RMSE), dan Mean Absolute Percentage Error (MAPE). Hasil penelitian ini menguji akurasi yang diperoleh secara linier dengan hasil korelasi yaitu kelas gagal (d) memiliki RMSE dan MAPE terkecil dengan nilai RMSE sebesar 1,148 dan MAPE sebesar 9,82% terhadap prestasi akademik siswa dalam matematika. Hasil analisis data menunjukkan bahwa variabel kegagalan berpengaruh positif terhadap G3, dimana nilai probabilitas dari uji F nilai signifikansi pengaruh kegagalan simultan terhadap G3 adalah 0,006 < 0,05 dan dari analisis koefisien determinasi diketahui bahwa variabel failuers signifikan terhadap variabel dependen dengan besar pengaruh 63,8 % (model 2).